2022
DOI: 10.1021/acsapm.2c00106
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Self-Limiting Electrospray Deposition Compositional Limits for Mechanically Tunable Polymer Composites

Abstract: Electrospray deposition (ESD) is a versatile micro-/nanocoating technology that utilizes the competition between the surface charge of a droplet and its surface tension to create monodisperse generations of micro-/nanodroplets. ESD can deposit uniform thin films by including dilute solutes in these droplets. One mode of ESD, self-limiting ESD (SLED), has been shown to exist when glassy polymers are sprayed in a volatile solvent below the polymer glass-transition temperature (T g). This leads to charge accumula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…[1] These droplets form due to competing interactions between surface tension and Coulombic repulsions. [2][3][4][5] ESD has been employed in several application areas, ranging from semiconductors to biotechnology, [6][7][8][9][10][11][12] as this process shows great promise as an emerging technology for surface coating applications. [1][2] With respect to photovoltaics and drug delivery, DOI: 10.1002/admi.202300982 ESD is particularly appealing for thin film coatings as it can effectively limit material loss as well as its facile production.…”
Section: Introductionmentioning
confidence: 99%
“…[1] These droplets form due to competing interactions between surface tension and Coulombic repulsions. [2][3][4][5] ESD has been employed in several application areas, ranging from semiconductors to biotechnology, [6][7][8][9][10][11][12] as this process shows great promise as an emerging technology for surface coating applications. [1][2] With respect to photovoltaics and drug delivery, DOI: 10.1002/admi.202300982 ESD is particularly appealing for thin film coatings as it can effectively limit material loss as well as its facile production.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] ESD is a technique notable for its ability to generate uniform polymer films with tunable morphologies. [5][6][7][8] Tunability, i.e., fine control of the microstructure, thickness, and porosity is achieved through manipulation of the electrospray parameters, such as input voltage, polymersolvent concentration, separation distance, and solution conductivity. 5,9 In the self-limiting electrospray deposition (SLED) regime, electrostatic charge build-up leads to the formation of conformal micron-scale porous coatings on 2D and 3D surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Tunability, i.e., fine control of the microstructure, thickness, and porosity is achieved through manipulation of the electrospray parameters, such as input voltage, polymersolvent concentration, separation distance, and solution conductivity. 5,9 In the self-limiting electrospray deposition (SLED) regime, electrostatic charge build-up leads to the formation of conformal micron-scale porous coatings on 2D and 3D surfaces. 4,6,10 The ability of SLED to coat both conductive and non-conductive surfaces is highly advantageous for coating various materials, with past and current examples including, most commonly, metals and semiconductors, but also glass, hydrogels, living tissue, and gold plated quartz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the spray of insulating polymers produces thickness-limited films in which the charge accumulation repels incoming spray droplets. 4,11,12 This self-limiting behavior enables the conformal coating of complex 3D surfaces. 13 Recent work from our group has shown that methylcellulose (MC) forms a self-limiting coating with a unique nanowire architecture when processed by ESD from water : ethanol solutions.…”
Section: Introductionmentioning
confidence: 99%